2018
DOI: 10.1111/acel.12796
|View full text |Cite
|
Sign up to set email alerts
|

Role of dietary amino acid balance in diet restriction‐mediated lifespan extension, renoprotection, and muscle weakness in aged mice

Abstract: SummaryExtending healthy lifespan is an emerging issue in an aging society. This study was designed to identify a dietary method of extending lifespan, promoting renoprotection, and preventing muscle weakness in aged mice, with a focus on the importance of the balance between dietary essential (EAAs) and nonessential amino acids (NEAAs) on the dietary restriction (DR)‐induced antiaging effect. Groups of aged mice were fed ad libitum, a simple DR, or a DR with recovering NEAAs or EAAs. Simple DR significantly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…It has been confirmed that H 2 S prevents the process of senescence in the endothelium [42], kidney [45,46], vascular [47], heart [48] and brain [43] of mice. Furthermore, increasing the content of endogenous H 2 S by proper diet extends the life span of the aged mice [49,50]. These previous findings offered a reasonable explanation for the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…It has been confirmed that H 2 S prevents the process of senescence in the endothelium [42], kidney [45,46], vascular [47], heart [48] and brain [43] of mice. Furthermore, increasing the content of endogenous H 2 S by proper diet extends the life span of the aged mice [49,50]. These previous findings offered a reasonable explanation for the results obtained in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…This is indicative of sulfhydration being more than just the presence of H2S modifying a protein, and suggests a more complicated systemic regulation of tissue-specific sulfhydrome maintenance either at baseline or when faced with a stressor, such as restricted food access. CGL deficiency limits the sulfhydrome under AL and DR feeding DR-enhanced H2S production capacity (Hine et al, 2015;Yoshida et al, 2018) (Figure 1D, E, J, and K), stress resistance (Hine et al, 2015), endocrine response , angiogenesis , and lifespan (Kabil et al, 2011a) requires CGL activity. Thus, we next tested the CGL requirement for diet-induced changes in the sulfhydrome.…”
Section: Dr Decreases Heart and Negligibly Impacts Plasma Sulfhydromementioning
confidence: 99%
“…A common molecular phenomenon amongst several dietary (Hine et al, 2015;Nakano et al, 2015;Yoshida et al, 2018), pharmaceutical (Wiliński et al, 2013), and genetic Wei and Kenyon, 2016) models of longevity is the increased production capacity and/or bioavailability of hydrogen sulfide (H2S) gas . H2S and its HSanion and S 2ion, herein referred simply as H2S, is historically classified as an environmental and occupational hazard due to its inhibition of mitochondrial respiration (Szabo et al, 2013;Wu et al, 2011) and lethality at elevated levels (Hendrickson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Independently of caloric intake, low-protein and high-carbohydrate diets were found to have the strongest extension of lifespan ( Solon-Biet et al., 2014 ). In addition to dietary protein restriction (PR), some studies suggest it is the restriction of essential amino acids (EAAs) that drive beneficial effects, given that supplementing dietary restriction with EAAs but not non-essential amino acids were sufficient to reverse prolongevity effects ( Grandison et al., 2009 ; Yoshida et al., 2018 ). Restriction of specific EAAs, such as the restriction of sulfur-containing amino acids (SAAs), methionine and cysteine, or methionine restriction (MR), and deficiency of the branched chain amino acids, leucine, isoleucine, and valine, or branched chain amino acid restriction (BCAAR), have been extensively characterized to increase metabolic homeostasis and promote healthy aging ( Fontana et al., 2016 ; Lee et al., 2016 ; Solon-Biet et al., 2014 ).…”
Section: Dietary Protein and Amino Acid Restrictionmentioning
confidence: 99%